2022
DOI: 10.1039/d1ma00858g
|View full text |Cite
|
Sign up to set email alerts
|

Highly-dispersed and high-metal-density electrocatalysts on carbon supports for the oxygen reduction reaction: from nanoparticles to atomic-level architectures

Abstract: Electrocatalyst for oxygen reduction reaction (ORR) is crucial for a variety of renewable energy applications (e.g., proton exchange membrane fuel cells, PEMFCs). The synthesis of highly-dispersed and high-metal-density ORR electrocatalysts...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 152 publications
(151 reference statements)
0
38
0
1
Order By: Relevance
“…At present, the hotspot research directions of SACs include the following: coordination environment (including the first coordination and adjacent environment), [17,18] molecular engineering (involving precursor molecular design and molecular catalyst grafting), [19,20] support engineering (for example, nanostructure design and defect structure regulation), [21,22] thermodynamic stability (such as thermal atomization in preparation and stability in application), [23,24] dynamic catalytic structures (dynamic change and plasticity of metal atoms in catalytic reaction process), [25,26] batch preparation (such as gram-level and kilogram-level preparation), [27,28] and ultrahigh content (limit loading on differentiated supports and site density/distance effect of metal atoms) [29,30] (see Figure 2 left for details). It is obvious that the SACs can be considered for mass production (batch preparation in industrial conditions) and practical applications when the foregoing five points are fully studied and optimized.…”
Section: The Significances Of This New Paradigm Of Afcsmentioning
confidence: 99%
See 4 more Smart Citations
“…At present, the hotspot research directions of SACs include the following: coordination environment (including the first coordination and adjacent environment), [17,18] molecular engineering (involving precursor molecular design and molecular catalyst grafting), [19,20] support engineering (for example, nanostructure design and defect structure regulation), [21,22] thermodynamic stability (such as thermal atomization in preparation and stability in application), [23,24] dynamic catalytic structures (dynamic change and plasticity of metal atoms in catalytic reaction process), [25,26] batch preparation (such as gram-level and kilogram-level preparation), [27,28] and ultrahigh content (limit loading on differentiated supports and site density/distance effect of metal atoms) [29,30] (see Figure 2 left for details). It is obvious that the SACs can be considered for mass production (batch preparation in industrial conditions) and practical applications when the foregoing five points are fully studied and optimized.…”
Section: The Significances Of This New Paradigm Of Afcsmentioning
confidence: 99%
“…Facing the complexities in the design of atomic-level heterogeneous catalysts, one can solve above bottleneck problems with SAC's libraries with widely adjustable metal loading (especially the ultrahigh-loading AFCs equipped by "dense site effects"). [29,30] In general, with the increase of metal content (that is shortening of site distance synchronously), the catalytic reactivity of metal atom catalysts is greatly enhanced (i.e., the specific reactivity depending on site density), which can further optimize the surface density of the metal atom (i.e., the design of AFCs with dense site effect) based on specific practical applications. [29] Taking the atomically dispersed metal sites with controllable surface density as a research object, researchers have deeply studied and revealed the origin of the enhancement of the activity of carbon-supported SACs at the sub-nano level with the increase of the distance between atom sites.…”
Section: Dense Site Effect Of Afcsmentioning
confidence: 99%
See 3 more Smart Citations